Subclinical neurocognitive dysfunction after carotid surgery under general and loco-regional anaesthesia - Tomašević, Boris (Array, 2009)
Carotid endarterectomy (CEA) has been generaly accepted as a safe method of stroke prevention with low occurrence of severe neurological complications. But the incidence of subclinical neurocognitive dysfunction after carotid surgery and its relation to the type of anesthesia remains unclear. Therefore, we made a comprehensive psychological testing of 40 patients undergoing CEA under general or loco-regional anaesthesia. S 100 β proten, which was found to be correlated with neurological damage, was also determined. 40 patients were randomly asigned to recieve either general anaesthesia or superficial cervical block. General anesthesia was induced by etomidate 0, 2 mg/kg and fentanyl 2 µg/kg and maintained with sevoflurane in the mixture of 50 % oxygen and nitous oxyde. Vecuronium 0, 08 mg /kg was used for muscle relaxation. Loco-regional anaesthesia patient group recieved superficial cervical block infiltrating 1, 5 mg/kg 0, 5 bupivacaine. Psychometric testing included Ravens progressive matrices, number recollection backwards and forwards and tests of spatial percepton and perception velocity. Patents were tested 24-48 hours before and 24 after surgery. All patients had uncomplicated clinical course. One patient in loco-regional group lost conscousness during carotid clamping, but recoverd after shunt insertion. The type of anaesthesia did not influence cognitive function in any test. S 100β protein level which was determined the time points of psychological testing, was not correlated with any psychometric test, either The duration of surgery and carotid clamping did not influence postoperative cognitive function. The only intraoperative variable relevant for neurocognitive function was shunt insertion. Analysis of variance for repeated measurements for anaesthesia and shunt as independent variables, and age and general intelligence as covariants, showed that patients with inserted shunt had significantelly worse results in tests of spatial perception (mean before 42, 7±36, 4, mean after 113, 2±112, 2). Among demographic data, age and general intelligence correlated with neurocognitive function. The cyper test was worse after surgery (mean before 32, 2±13, 1, mean after 31, 2±14, 92) and results correlated only with general intelligence (F=5, 3 ; r=0.42, p<0, 5). Test of concentration after surgery negatively correlated only with age (F=7, 2 ; r=-0.45, p<0, 5). Conclusion: 1.The type of anaesthesia did not influence neurocognitive function 24 after carotid endarterectomy. 2. Shunt insertion is the only intraoperative variable related to subclinical neurocognitive dysfunction - worse results in tests of spatial perception. 2. Age and general intelligence are the only demographic date related to postoperative neutrocognitive function. Cypher test, althoug worse after surgery, was better in patients with higher general intelligence, and test of concentration was worse in older patients.